1986
DOI: 10.1111/j.1539-6924.1986.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Modeling of Animal Bioassay Data with Variable Dosing Regimens: Example—Vinyl Chloride

Abstract: We consider animal bioassay experiments with variable dosing regimens in which groups of animals are dosed beginning at different ages and for varying durations. Two response models are discussed and then applied to data from an experiment on vinyl chloride exposure of F-344 rats, B6C3F1 and Swiss CD-1 mice, and Syrian Golden hamsters. The multistage model of Armitage and Doll, as extended by Whittemore, Day and Brown, and Crump and Howe, is used to estimate the dose effect on the ordered stages of tumor devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Considerable past work has emphasized the potential for age-related differences in long-term risks from carcinogenic exposures that could result from early- versus late-life exposure to carcinogens that tend to cause mutations at a single stage that is either early or late in the multistage molecular pathologic sequence of genetic changes (Brown and Hoel 1986; Day and Brown 1980; Whittemore 1977). In general, carcinogenic risks will tend to be greater for early-life exposure to a carcinogen that causes relevant early-stage transitions but will tend to be greater for late-life exposure to a carcinogen that causes relevant late-stage transitions.…”
Section: Mapping Rodent Life Stages To Human Periods: Implications Fomentioning
confidence: 99%
“…Considerable past work has emphasized the potential for age-related differences in long-term risks from carcinogenic exposures that could result from early- versus late-life exposure to carcinogens that tend to cause mutations at a single stage that is either early or late in the multistage molecular pathologic sequence of genetic changes (Brown and Hoel 1986; Day and Brown 1980; Whittemore 1977). In general, carcinogenic risks will tend to be greater for early-life exposure to a carcinogen that causes relevant early-stage transitions but will tend to be greater for late-life exposure to a carcinogen that causes relevant late-stage transitions.…”
Section: Mapping Rodent Life Stages To Human Periods: Implications Fomentioning
confidence: 99%
“…Both angiosarcomas and carcinomas in liver were observed. These data have been used to show that VC affects the first stage of a five-stage carcinogenesis by Brown and Hoel (1986). This information, along with the carcinogenic potency estimate calculated on the basis of the Maltoni et al study, are used to predict the tumor incidence rates observed in the study.…”
Section: Tumor Incidence and The Corresponding Metabolized Dose For Amentioning
confidence: 99%
“…In their analysis of data on angiosarcoma incidence from the drew et al (1983) study, Brown and Hoel (1986) concluded that VC appears to affect the first stage of a multistage (five-stage) carcinogenesis. This conclusion is consistent with the observation from an epidemiologic study prepared by Wong and Wharton (1986) for the Chemical Manufacturers Association (CMA).…”
Section: Evaluation Of Risk Estimate From Lifetime Bioassay Data Agaimentioning
confidence: 99%
“…(1)(2)(3) The multistage model, proposed by Armitage and Doll" to explain the observation that the age-specific incidence rates of many cancers increase with a power of age, views the process of carcinogenesis as the progressive deterioration of a normal cell through a sequence of intermediate stages to malignancy. When a couple of crucial approximations are made, the Armitage-Doll model generates an incidence function that increases with a power of age.…”
mentioning
confidence: 99%